Researchers' experience with project management in health and medical research: Results from a post-project review - Payne, J.; France, K.; Henley, N.; D'antoine, Heather; Bartu, Anne; Elliott, E.; Bower, C. (BioMed Central Ltd, 2011)
Background: Project management is widely used to deliver projects on time, within budget and of defined quality. However, there is little published information describing its use in managing health and medical research projects. We used project management in the Alcohol and Pregnancy Project (2006-2008) http://www.ichr.uwa.edu.au/alcoholandpregnancy and in this paper report researchers' opinions on project management and whether it made a difference to the project. Methods: A national interdisciplinary group of 20 researchers, one of whom was the project manager, formed the Steering Committee for the project. We used project management to ensure project outputs and outcomes were achieved and all aspects of the project were planned, implemented, monitored and controlled. Sixteen of the researchers were asked to complete a self administered questionnaire for a post-project review. Results: The project was delivered according to the project protocol within the allocated budget and time frame. Fifteen researchers (93.8%) completed a questionnaire. They reported that project management increased the effectiveness of the project, communication, teamwork, and application of the interdisciplinary group ofresearchers' expertise. They would recommend this type of project management for future projects. Conclusions: Our post-project review showed that researchers comprehensively endorsed project management in the Alcohol and Pregnancy Project and agreed that project management had contributed substantially to the research. In future, we will project manage new projects and conduct post-project reviews. The results will be used to encourage continuous learning and continuous improvement of project management, and provide greater transparency and accountability of health and medical research. The use of project management can benefit both management and scientific outcomes of health and medical research projects.